PENGGUNAAN LEMBAR KERJA SISWA UNTUK MENINGKATKAN MINAT BELAJAR PADA KOMPETENSI DASAR MENGOLAH KUE INDONESIA - Marline Pakpahan (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This study aims to (1) determine the implementation of the use of Student Worksheets (LKS) to increase learning interest in basic competencies in processing Indonesian cakes at SMK Negeri 6 Bungo. (2) Knowing the increasing interest in learning of SMK Negeri 6 Bungo students after using student worksheets on the basic competencies of Indonesian cakes. This type of research is classroom action research with two cycles and each using 4 steps, namely: planning (Plan), action (Action), observation (Observation), and reflection (Reflection) which was carried out from March 2021 until May 2021. The object of the research is class XI Catering SMK Negeri 6 Bungo as many as 31 students. Data collection techniques using questionnaires, observation, and documentation. The instrument was read by the principal of SMK Negeri 6 Bungo. The results showed: 1) The implementation of the use of Student Worksheets to increase learning interest in the basic competencies of processing Indonesian cakes at SMK Negeri 6 Bungo can run smoothly, this can be seen from the attendance of students in the first cycle of 92.68% from 41 people to 95 ,12%, all read and work on the theoretical and practical questions available on the student worksheets. 2) Increased student interest in learning, seen in the questionnaire before using the LKS student interest was 65%, after using the LKS student interest in learning became very high 15% and high 85%.